Regional assessment of short-term impacts of corn stover removal for bioenergy on soil quality and crop production - Kenney, Ian T. (Kansas State University, 2011)
The U.S. agricultural sector is in a prime position to provide crop residues such as corn (Zea mays L.) stover as feedstock for large-scale bioenergy production. While producing renewable energy from biomass resources is a worthy initiative, excessive removal of corn stover from agricultural fields has the potential to increase soil erosion, degrade soil properties, and reduce corn yields. A need exists to objectively assess stover removal impacts on agriculture and the environment on regional scales. This project assessed the effects of removing various rates of corn stover on runoff and erosion and changes in soil physical properties and corn yields on a regional scale across three soils at Colby, Hugoton, and Ottawa in Kansas, USA. The soils were Ulysses silt loam (Fine-silty, mixed, superactive, mesic Aridic Haplustolls) at Colby, Hugoton loam (Fine-silty, mixed, superactive, mesic Aridic Argiustolls) at Hugoton, and Woodson silt loam (Fine, smectitic, thermic Abruptic Argiaquolls) at Ottawa, all with slopes [less than or equal to] 1%. Five stover treatments were studied that consisted of removing 0, 25, 50, 75, and 100% of stover after harvest from no-till and strip-till continuous corn plots. Simulated rainfall was applied in spring 2010 at rates representing 5 yr return intervals at each site and included a dry and wet run. Runoff increased with an increase in stover removal at Colby and Hugoton, but not at Ottawa. At Colby, stover removal rates as low as 25% caused runoff to occur 16 min sooner and increased sediment loss. At this site, runoff and sediment-carbon (C) loss increased as removal rates exceeded 25%. At Hugoton, complete stover removal increased loss by total N by 0.34, total P loss by 0.07, PO[subscript]4-P by 0.003 and NO[subscript]3-N by 0.007 kg ha-[superscript]1. At Ottawa, PO[subscript]4-P loss decreased by 0.001 kg ha-[superscript]1 with 25% removal and by 0.003 kg ha-[superscript]1 with 50% removal. Mean weight diameter (MWD) of wet aggregates decreased with an increase in stover removal on all soils. At Ottawa, stover removal at 75% reduced soil C in the top 5 cm by 1.57 Mg ha-[superscript]1. Soil volumetric water content decreased with stover removal at Colby and Ottawa, but was variable at Hugoton. Soil temperature tended to increase with stover removal during summer months and decrease during winter months. Soil temperature also fluctuated much more widely with stover removal, resulting in more freeze-thaw events compared to no stover removal. No effect of stover removal on soil water retention was observed on any of the soils. In 2009, removal rates [greater than or equal to]50% resulted in greater grain yield at Colby, while removal rates [greater than or equal to]75% resulted in greater grain yields at Ottawa in 2009 and 2010. Results from the first two years of stover management suggest that stover removal at rates above 25% for bioenergy production increased water erosion, degraded soil structural properties, and altered soil water and temperature regimes. Higher rates of removal ([greater than or equal to]75%) can also reduce soil C concentration in the short-term in rainfed regions. However, grain yields may be enhanced by stover removal from irrigated soils and from rainfed soils with adequate moisture. Overall, the increase in water erosion and alteration in soil properties in the short-term suggest that stover removal can detrimentally affect water quality and soil productivity in Kansas. Further long-term monitoring is warranted to conclusively discern stover removal implications.
Keywords: Stover; Bioenergy; Soil; Erosion; Agriculture; Management; Agronomy (0285); Energy (0791); Soil Sciences (0481)